104k views
1 vote
Find the derivative. f(x) = e^(x) cosh(x)

User Stuartd
by
5.5k points

1 Answer

4 votes

We are given


f(x)=e^(x) cosh(x)

Since,
e^(x) and
cosh(x) are multiplied

so, we will use product rule of derivative


\mathrm{Apply\:the\:Product\:Rule}:\quad \left(f\cdot g\right)'=f\:'\cdot g+f\cdot g'


f'(x)=(d)/(dx)\left(e^x\right)\cosh \left(x\right)+(d)/(dx)\left(\cosh \left(x\right)\right)e^x

we know that


(d)/(dx)\left(e^x\right)=e^x

and


(d)/(dx)\left(\cosh \left(x\right)\right)=\sinh \left(x\right)

so, we can plug these values

and we get


f'(x)=e^x\cosh \left(x\right)+\sinh \left(x\right)e^x...............Answer

User Whyyie
by
5.2k points